Designing digital systems for rehabilitation practices - Gunnar Ellingsen; Cathrine Arntzen; Lina Forslund; Morten Nikolaisen; Marianne Eliassen; Astrid Gramstad; Unn Manskow (Tidsskrift for Omsorgsforskning)
The trajectories of patients in need of long-term rehabilitation services are extremely complex. Therefore, strengthening the rehabilitation field requires increasing organizational resilience to ensure robust processes and efficient collaboration and communication. In this study, we explored how digital systems can promote organizational resilience in rehabilitation practices. Methodologically, we applied an experience-based co-design approach in which we held three day-long creative workshops with approximately 40 participants each in 2021 and 2022. The goal was to design a digitally supported model for the care and rehabilitation of patients with acquired brain injuries. This paper presents the themes related to digitalization that emerged from the discussions in the workshops. The paper develops the argument that designing digital systems for resilient rehabilitation practices is far more than merely a technical issue. It requires broad sociopolitical engagement to put rehabilitation on the political agenda, and designers need to take a stance on both organizational and ethical issues. Analytically, we draw on the theoretical concept of information infrastructure and the theoretical concept of articulation work.